On the relationship between a 2 x 2 matrix and second-order scalar spectral problems for integrable equations - Kamchatnov, A. M.; Kraenkel, Roberto André [UNESP] (Iop Publishing Ltd, 2002)
A simple proof is given that a 2 x 2 matrix scheme for an inverse scattering transform method for integrable equations can be converted into the standard form of the second-order scalar spectral problem associated with the same equations. Simple formulae relating these two kinds of representation of integrable equations are established.